Human’s natural responsibility - Kruszyński, Rafał Jerzy (Acta Universitatis Lodziensis. Folia Iuridica, 2015)
The study deals with a phenomenon of responsibility. It distinguishes between natural responsibility and moral responsibility or legal responsibility (liability). The central intention of the text is to reveal that responsibility does not refer only to moral or legal dimensions. The natural responsibility is greater (more important) than the moral responsibility or legal one. What is more, both the moral responsibility and the legal responsibility are changeable. The natural responsibility instead, is constant and concerns all the mankind in the same way.